Fractal Analysis of Dynamics of Coefficients of a Financial Standing of the Company - Irina Yurevna Motorina; Vladimir Anatolyevich Kurzenev (Управленческое консультирование)
In the article the general analysis of emergence of bankruptcy is carried out, it is offered to forecasting of bankruptcy apply methods of the fractal analysis, which basis principle is self-similarity, alternative to the statistical analysis. Operability of a method is approved on branch statistics of the North-Western Federal District.